Cancer-specific innate and adaptive immune rewiring drives resistance to PD-1 blockade in classic Hodgkin lymphoma - Julia Paczkowska; Ming Tang; Kyle T. Wright; Li Song; Kelsey Luu; Vignesh Shanmugam; Emma L. Welsh; Jason L. Weirather; Naomi Besson; Harrison Olszewski; Billie A. Porter; Kathleen L. Pfaff; et al. (Nature Communications)
Abstract Hodgkin Reed-Sternberg (HRS) cells of classic Hodgkin lymphoma (cHL), like many solid tumors, elicit ineffective immune responses. However, patients with cHL are highly responsive to PD-1 blockade, which largely depends on HRS cell-specific retention of MHC class II and implicates CD4+ T cells and additional MHC class I-independent immune effectors. Here, we utilize single-cell RNA sequencing and spatial analysis to define shared circulating and microenvironmental features of the immune response to PD-1 blockade in cHL. Compared with non-responders, responding patients have more circulating CD4+ naïve and central memory T cells and B cells, as well as more diverse CD4+ T cell and B cell receptor repertoires. Importantly, a population of circulating and tumor-infiltrating IL1β+ monocytes/macrophages is detectable in patients with cHL but not healthy donors, and a proinflammatory, tumor-promoting signature of these circulating IL1β+ monocytes is associated with resistance to PD-1 blockade in cHL. Altogether, our findings reveal extensive immune rewiring and complementary roles of CD4+ T cells, B cells and IL1β+ monocytes in the response to PD-1 blockade and suggest that these features can be captured with a peripheral blood test.